Toward direct determination of conformations of protein building units from multidimensional NMR experiments VI chemical shift analysis of his to gain 3D structure and protonation state information - Hudáky, Péter (Journal of computational chemistry, 2005)
(c) 2005 Wiley Periodicals, Inc. J Comput Chem 26: 1307-1317, 2005.